The contemporaneousness of The Capital - Gorender, Jacob (Pontifícia Universidade Católica de São Paulo, 2004)
This article, based on a conference which took place on 5/19/93at PUC-SP, aims to demonstrate the existence of a close relationshipbetween the theoretical formulations in The Capital by Karl Marx andthe central characteristics of the present phase of capitalism.